You Can't Change What You Don't See: Developing New Teachers' Political Understanding of Education. (July 2013) - Picower, Bree
Many teachers who enter the profession to "make a difference" do not realize education is a highly political field. This qualitative study examined how teacher education can support new teachers to develop a critical sociopolitical analysis of education. The findings indicate through a year-long course of study, teachers developed two new awarenesses about education. They (1) recognized that everything within education was political and because of this they (2) realized that they had more to learn. The overarching awareness about the political nature of education supported them to recognize four connected insights: (1) certain groups benefit from current structures while (2) others are oppressed, (3) parents and community members should have power in educational decisions that affect them, and (4) race plays a systemic role in all of the above. Within the awareness of realizing they had more to learn, three new stances emerged. Teachers started to (1) reexamine their prior knowledge, (2) realize they needed to hear multiple perspectives before forming opinions, and (3) analyze the political motivation of people providing information. By recognizing that everything is political and by taking a questioning stance, the findings indicate that the teachers reframed their analysis in five key ways. Teachers (1) moved from a focus on individual blame to a focus on systemic inequality; (2) from an ethnocentric perspective to culturally relevant pedagogy; (3) from viewing teachers as holders of power to facilitators who share power; (4) from seeing community deficits to seeing strengths; (5) and from feeling isolated to feeling connected.